PREPARASI NANOPARTIKEL GAMAVUTON-0 MENGGUNAKAN KITOSAN RANTAI PENDEK DAN TRIPOLIFOSFAT SEBAGAI CROSS LINKER SERTA UJI CELLULAR UPTAKE PADA KULTUR SEL MCF-7 SECARA IN VITRO - , Wintari Taurina, Dr. rer.nat. Ronny Martien, M.Si. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
GVT-0 is a modified compound of curcumin molecules with potential anti-inflammatory and analgesic. Currently, administration of the compound GVT-0 by parenteral route is limited, because the compound bioaviability per oral administration is low. It caused by the physicochemical properties of drugs which are not profitable because of hydrophilicity, molecular size, and density of negative charge, so it has a poor intestinal permeability. The limitation can be overcame by nanoparticle system. The aims of this study are to develop a nanoparticle carrier of GVT-0 with a low viscous chitosan as a system of per ora drug delivery system and also to test their cellular uptake ability. In this study, GVT-0 nanoparticles formulated using the method ionotropic gelation by the addition of a negatively charged TPP. Nanoparticles will be characterized using TEM and PSA to see their morphology and size, then tested the stability in the HCL 0,1 N pH 1 and AIF and the ability of cellular uptake in MCF 7 cells cultured in vitro. GVT-0 nanoparticles which are made have a average of particle size between 504,7 nm - 724,4 nm and generally have a spherical shape. The entrapment efficiency result between 30,27% - 76,67%. GVT-0 nanoparticle is relatively stable in HCl 0,1 N pH 1 until the third hour on stability between 53,03 - 83,56%, and in AIF until the fourth hour on stability between 63,08 - 97,08%. The observation of cellular uptake into MCF-7 in vitro on fluorescent microscopy demonstrated GVT-0 capable of entering into cells. Based on the results of the studies, it appears that the GVT-0 can be preparated as GVT-0 nanoparticles with low viscous chitosan. The GVT-0 nanoparticles is stable in HCl 0,1 N at pH 1 and AIF, and able to enter the cell.